Educational Word Box Game Tool To Enhance Cognitive Development In Early Childhood - Nurqodriah, Yuyu; Widjayatri, RR. Deni; Mercury Kiwonde, Flora (Indonesian Journal of Early Childhood Educational Research (IJECER), 2023)
This study aims to investigate the improvement of cognitive abilities in early childhood by utilizing the educational game "Word Box." The research employs a qualitative descriptive approach, with data collection methods including Documentation, Interviews, and Observations. Data analysis follows the Miles and Huberman model. The results indicate that the utilization of the educational game "Word Box" has a positive impact on the cognitive development of children through their interaction with the game. There is a significant improvement in cognitive aspects, such as memory skills, understanding, and language usage in children.┬á┬á